2016
DOI: 10.7314/apjcp.2015.16.18.8553
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Biodosimetry: Quantitative Assessment of Radiation Dose with Total Body Exposure of Rats

Abstract: Background: Accurate dose assessment and correct identification of irradiated from non-irradiated people are goals of biological dosimetry in radiation accidents. Objectives: Changes in the FDXR and the RAD51 gene expression (GE) levels were here analyzed in response to total body exposure (TBE) to a 6 MV x-ray beam in rats. We determined the accuracy for absolute quantification of GE to predict the dose at 24 hours. Materials and Methods: For this in vivo experimental study, using simple randomized sampling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For MRM-HR profiling of mOMSA, peptides containing each oxidatively modified amino acid residue were standardized against the peak area value of the corresponding unmodified peptide and analyzed for correlation with the radiation exposure dose as a relative peak area ratio. The fitting of quadratic equations was investigated for each mOMSA; in fact, most human genes show quadratic dose response to radiation [ 16 , 17 ]. In the in vivo model, eleven sequences showed significant dose-dependent correlations ( r value) of >0.5 by linear or curve fitting.…”
Section: Resultsmentioning
confidence: 99%
“…For MRM-HR profiling of mOMSA, peptides containing each oxidatively modified amino acid residue were standardized against the peak area value of the corresponding unmodified peptide and analyzed for correlation with the radiation exposure dose as a relative peak area ratio. The fitting of quadratic equations was investigated for each mOMSA; in fact, most human genes show quadratic dose response to radiation [ 16 , 17 ]. In the in vivo model, eleven sequences showed significant dose-dependent correlations ( r value) of >0.5 by linear or curve fitting.…”
Section: Resultsmentioning
confidence: 99%
“…(continued.) methodology), teams used only 1-4 genes [54,[64][65][66][67][68][69][70][71][72][73]. Large scale inter-laboratory comparison exercises initiated from NATO research task groups or the European biodosimetry network (RENEB) confirmed the applicability of this approach [74][75][76][77].…”
Section: Ge Biomarkers For Retrospective Biodosimetrymentioning
confidence: 90%
“…IFN-gamma) replaced these so called 'immediate early (proto-onco) genes' [50][51][52][53]. GADD45 (Growth arrest and DNA damage gene [54]) was one of the earliest TP53 related genes and many more were examined in the following decades [50].…”
Section: Ge Biomarkers For Retrospective Biodosimetrymentioning
confidence: 99%
See 2 more Smart Citations